Speedliter's handbook : learning to craft light with Canon Speedlites - Arena, Syl (Peachpit, 2011)
Getting your Canon Speedlite to produce the light you need can be a real challenge. For those new to flash photography--or for anyone who has previously given up out of frustration-- Speedliter's Handbook is a revelation. Photographer Syl Arena takes you on a journey that begins with an exploration of light and color, moves through a comprehensive discussion of the Canon Speedlite family and all of the accessories and equipment available to the Speedliter, then settles down to crafting great light in one photo shoot after another. Whether you want to create a classical portrait, shoot an event, or simply add a little fill light to a product shot, Speedliter's Handbook shows you how. A fantastic in-depth resource illustrated with over 500 images, Speedliter's Handbook covers: how to see the various characteristics and properties of light itself, as well as the differences between how your camera sees versus how you see all the buttons and dials of the entire Canon Speedlite family the basics of on-camera flash...and the necessity of getting your flash off the camera how to beautifully balance flash with the existing ambient light all the equipment necessary for great Speedlite shots how to get amazing shots with just one Speedlite how and when to use E-TTL versus manual flash the use of color gels to balance color, as well as create dramatic effects how to tame the sun--or any really bright light--with hi-speed sync and much, much more Whether you're shooting portraits, events, or sports, Speedliter's Handbook is an essential resource that teaches you how to craft the light you need for any type of shot you want.